(untitled) (Applied Biological Research, 2017)
Early and late blight are the two major biological constraints that hamper the yield and quality of tomato. Twelve different treatments, comprising of solo and combination doses of zoxamide with cymoxanil and mancozeb were evaluated against these diseases for two consecutive rabi seasons. The pooled data revealed that in these two seasons, the combination of zoxamide 33% + cymoxanil 33% WP at the dose of 600 g ha-1 gave best control of both early and late blight diseases as compared to untreated check, manifesting 68.7 and 77.5% control, respectively. Similarly, the combination of zoxamide 8.3% + mancozeb 66.7% WP @ 2500 g ha-1 gave best control of both the diseases as compared to untreated check manifesting a control of 62.5 and 65.3%, respectively. None of the doses of zoxamide 8.3% + mancozeb 66.7% WP and zoxamide 33% + cymoxanil 33% WP was phytotoxic to tomato plants.